Association of Time Between Left Ventricular and Aortic Systolic Pressure Peaks With Severity of Aortic Stenosis and Calcification of Aortic Valve - Sato, Kimi (JAMA Cardiol, 2019)
IMPORTANCE: Diagnosis of low-gradient severe aortic stenosis (AS) is challenging. We hypothesized that the time between left ventricular (LV) and aortic systolic pressure peaks (T(LV-Ao)) is associated with aortic stenosis (AS) severity and may have additive value in diagnosing severe AS, especially in patients with low-gradient AS. OBJECTIVE: To investigate the diagnostic utility of measuring catheter-based T(LV-Ao) in patients with severe AS. DESIGN, SETTING, AND PARTICIPANTS: We studied 123 patients with severe AS at the Cleveland Clinic Foundation, a tertiary referral center, who underwent transcatheter aortic valve replacement (TAVR) via femoral access and had pre-TAVR cardiac computed tomography assessment and hemodynamic measurements recorded during a TAVR procedure. All patients received hemodynamic evaluation, echocardiographic assessment, and quantification of aortic valve calcification (AVC) by multidetector computed tomography. Hemodynamic data were collected via left heart catheterization done just before TAVR, and T(LV-Ao) was calculated offline. Data were analyzed between October 5, 2015, and July 20, 2016. MAIN OUTCOMES AND MEASURES: The association between T(LV-Ao) and AVC or other conventional imaging parameters was analyzed. RESULTS: Of the included patients, the mean (SD) age was 81 (9) years, and 65 (54%) were men (54%). Among 123 patients, 48 patients (39%) had low-gradient AS (<40 mm Hg) and mean (SD) T(LV-Ao) was 69 (39) milliseconds. In multivariable logistic regression analyses, higher T(LV-Ao) (odds ratio [OR], 1.02; 95% CI, 1.01-1.04; P = .002) and higher peak aortic valve (AV) velocity (OR, 1.01; 95% CI, 1.00-1.02; P = .008) were independently associated with severe AVC (AVC >1000 AU). Adding T(LV-Ao) to the peak AV velocity and AV area showed significant incremental value to be associated with AVC, with a net reclassification improvement of 0.61 (95% CI, 0.23-0.99; P = .002) and integrated discriminatory improvement of 0.09 (95% CI, 0.03-0.16; P = .003). In a subgroup of patients with low-grade AS, higher T(LV-Ao) was the only parameter associated with severe AVC (OR, 1.02; 95% CI, 1.001-1.04; P = .03). CONCLUSIONS AND RELEVANCE: Prolonged T(LV-Ao) was associated with severe AVC. This catheter-based hemodynamic index may be an additional surrogate to differentiate low-gradient true severe AS. Larger, prospective studies investigating the role of T(LV-Ao) as a marker of clinical outcomes in patients undergoing TAVR are required.